Plasma Pre-treatment of Large Surface Areas Using a LARGE Plasma source Grobflächige Plasmavorbehandlung und PECVD bei Atmosphärendruck mittels LARGE-Plasmaquelle - Kotte, Liliana; Mäder, Gerrit; Roch, Julius; Leupolt, Beate; Kaskel, Stefan; Wielant, Jan; Mertens, Tobias; Gammel, Franz J. (Galvanotechnik, 2013)
Using the LARGE (Long Arc Generator) plasma source, a long arc, forming a fan-shaped afterglow plasma with a width of 80 to 350 mm is formed at atmospheric pressure. In contrast to most point-form atmospheric plasma sources, the method offers an attractive means for pre-treatment of large surface areas. The reactive working gas formed by plasmachemical excitation can be used to activate or modify the surfaces of materials ranging from metals to polymers. In this article, the operation of the LARGE plasma source, the means by which coating properties can be modified and its use to deposit SiOx adhesion-promoting layers on metals are described. Of special interest were the optical properties and the morphology of these deposits as well as their potential as adhesion-promoters in metal-plastic composite structures. Because of its very flexible stand-off distance of up to 60 mm and its compact construction, LARGE technology is ideal for a wide range of industrial applications. These include coating of 2.5 D components, and formation of nano-structured SiOx layers for mechanical and chemical bonding of epoxy adhesives to surfaces.
CRIS-Team Scopus Importer:2023-03-20